2011
DOI: 10.1111/j.1600-0528.2011.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health condition of French elderly and risk of dementia: a longitudinal cohort study

Abstract: Having eleven or more missing teeth seemed to be associated with a lower risk of dementia in people with lower education possibly owing to the suppression of source of chronic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
159
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(169 citation statements)
references
References 24 publications
5
159
1
4
Order By: Relevance
“…Furthermore, periodontal disease exposure in earlier studies has been assessed with measures, such as the community periodontal index (CPI), which are based on clinical signs that do not provide much information about the underlying biology of periodontal disease (7). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, periodontal disease exposure in earlier studies has been assessed with measures, such as the community periodontal index (CPI), which are based on clinical signs that do not provide much information about the underlying biology of periodontal disease (7). …”
Section: Introductionmentioning
confidence: 99%
“…When severe, such impairments can lead directly to malnutrition, impacting the prognosis and increasing the burden on caregivers [67,68]. Also, factors such as declines in awareness and behaviors related to oral hygiene, difficulty in carrying out oral care and eating soft food due to declines in eating and swallowing functions clearly increase the risk of periodontal disease [69] (shown schematically in Fig. 1).…”
Section: Prospects For Research Into Mastication and Dementia Among Tmentioning
confidence: 98%
“…These researchers recommended further studies in this field. In a study, no relationship was observed between oral hygiene and cognitive decline in geriatrics (7). Although some studies were conducted to assess oral health in the elderly, in our country, currently, there is insufficient evidence to develop recommendations for strategies to improve cognitive status among the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…The results from some recent studies indicate a mild to moderate relationship between oral health as well as cognitive disorders (5). The reaction of the immune system to oral and dental bacteria seems resulted in the death of nerve cells or attenuation of memory (6,7). According to some studies, reduced number of teeth is associated with increased incidence of cognitive decline (5,8).…”
Section: Introductionmentioning
confidence: 99%